2011
DOI: 10.1021/bi200382c
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Folding and Stability of the HET-C2 Glycolipid Transfer Protein Fold: Does a Molten Globule-like State Regulate Activity?

Abstract: The glycolipid transfer protein (GLTP) superfamily is defined by the human GLTP-fold which represents a novel motif for lipid binding/transfer and for reversible interaction with membranes, i.e. peripheral amphitropic proteins. Despite limited sequence homology with human GLTP, we recently showed that HET-C2 GLTP of Podospora anserina is organized conformationally as a GLTP-fold. Currently, insights into the folding stability and conformational states that regulate GLTP-fold activity are almost nonexistent. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…Precisely which molecular events lead to fusion avoidance and death of contacting fungal hyphae is not currently known, but it has been suggested that a conformational change, in the case of HET-C2, may be important to initiate an apoptotic response [66].…”
Section: Discussionmentioning
confidence: 99%
“…Precisely which molecular events lead to fusion avoidance and death of contacting fungal hyphae is not currently known, but it has been suggested that a conformational change, in the case of HET-C2, may be important to initiate an apoptotic response [66].…”
Section: Discussionmentioning
confidence: 99%
“…What is clear is that the localized changes to the glycolipid recognition center in apo-HET-C2 have marginal impact on protein temperature stability. At neutral pH, the unfolding transition temperature mid-point for HET-C2 is ~49 °C (Kenoth et al 2011), which is only 4–5 °C lower than that of human GLTP (Kamlekar et al 2010). The two Cys residues, i.e.…”
Section: Structural ‘Tweaks’ Linked To Altered Glycolipid Specificmentioning
confidence: 94%
“…heterokaryon incompatibility C2 protein (HET-C2) of Podospora anserina and GLTP in the thermoacidophilic unicellular red alga, Galdieria sulphuraria (PDB: 2I3F) show GLTP-folds with putative lipid recognition centers containing the same essential residues topologically organized in the same way as in mammalian GLTPs complexed with glycolipid (Kenoth et al 2010, 2011; Samygina et al 2011). In the case of HET-C2, functional analyses show more focused glycolipid selectivity than exhibited by human GLTP such as fast transfer of glucosylceramide (GlcCer) or GalCer but almost no transfer of 3-sulfo-GalCer (sulfatide).…”
Section: Structural ‘Tweaks’ Linked To Altered Glycolipid Specificmentioning
confidence: 99%
“…Yet, ACD11 is unable to transfer glycolipids (Brodersen et al, 2002), consistent with the lack of essential residues needed for glycosphingolipid (GSL) sugar headgroup binding (Petersen et al, 2008). In mammalian GLTPs and HET-C2 fungal GLTP, X-ray structures reveal the molecular details of how glycolipids are recognized and bound by a conserved residue cluster (Asp, Asn, Lys, His, Trp) that form a hydrogen bond network with the GSL sugar-amide region, thus explaining the selectivity and transfer proficiency for various GSLs (Airenne et al, 2006; Kenoth et al, 2011; Kenoth et al, 2010; Malinina et al, 2006; Malinina et al, 2004; Samygina et al, 2011). Currently lacking for ACD11 is establishment of its preferred sphingolipid ligand as well as direct evidence for its functional involvement in the regulation of plant sphingolipid metabolism.…”
Section: Introductionmentioning
confidence: 99%